Kajian terhadap Model Pembelajaran Tenis Meja Berbasis Drill untuk Siswa SMKN 1 Patilanggio Pohuwato - Indra Dwi Restuaji; Hariadi Said; Mirdayani Pauweni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The aim of this study was to examine the appropriate drill-based learning model for students at SMKN 1 Patilanggio. To achieve this objective, a qualitative descriptive method with literature review technique was applied to describe the application of drills in table tennis learning at the senior high school level. The findings of this study included six relevant articles from a search of articles published between 2017 and 2025. These findings are insufficient to serve as a source of study for drill-based table tennis learning models. However, researchers can develop theories by utilizing the findings of previous researchers. In this case, researchers must set limitations on articles as a form of caution in creating this learning model so that it is appropriate for use by students at SMK Negeri 1 Patilanggio Pohuwato. Keywords: Learning Model, PJOK, Table Tennis, Vocational High School Students.